The effect of age on anastomotic leakage in colorectal cancer surgery: A population‐based study. Issue 1 (7th June 2018) - Zaimi, Ina; Sparreboom, Cloë L.; Lingsma, Hester F.; Doornebosch, Pascal G.; Menon, Anand G.; Kleinrensink, Gert‐Jan; Jeekel, Johannes; Wouters, Michel W. J. M.; Lange, Johan F.; ,
Abstract : Background: The aim of this study was to investigate the effect of age on CAL and its associated mortality. Methods: Data were derived from the Dutch ColoRectal Audit. All patients undergoing resection for colorectal cancer in the Netherlands between January 2011 and December 2016 were included. Univariable and multivariable logistic regressions were performed to test the effect of age on CAL and its associated mortality. Results: In total, 45 488 patients were included. The incidence of CAL was 6.4% in patients <60 years old, 5.5% in patients 60‐69 years old, 5.4% in patients 70‐80 years old, and 4.9% in patients ≥80 years old ( P < 0.001). Multivariate analysis showed that age was protective for CAL (OR 0.965 per 5 years, 95% CI 0.941‐0.985, P < 0.001). Mortality after CAL was 1.3% in patients <60 years old, 4.8% in patients 60‐69 years old, 12.3% in patients 70‐80 years old, and 27.0% in patients >80 years old ( P < 0.001). Older age was associated with mortality following CAL (OR 1.497 per 5 years 95% CI 1.364‐1.647, P < 0.001). Conclusions: This population‐based study suggests a protective effect of increased age on CAL after colorectal cancer resection. However, older age is strongly associated with mortality after CAL.